Job Satisfaction in the Workplace Systematic Literature Review (SLR) - Agnes Dinda P (Jurnal Indonesia Sosial Teknologi, 2024)
Job satisfaction and employee performance have become a significant research focus in management globally. It is a crucial concern for organisations to evaluate individual achievements in the context of work. Employee performance evaluation is based on their ability to execute their tasks in a way that contributes to achieving organisational goals and creates satisfaction within the scope of their work. This research applies a Systematic Literature Review (SLR) methodology that integrates several previous studies for further analysis. Through a preliminary study, articles in reputable journals, such as the Scopus database index, were selected and compiled. The findings highlighted that employees' attitudes and performance in the work environment are influenced by their level of satisfaction with their jobs. This systematic literature review provides an up-to-date overview of job satisfaction and employee relations. In analysing 24 published articles, it was found that the main factors influencing job satisfaction include human resources, employee relations, and work environment. In addition, the articles proposed various ways to improve job satisfaction, such as performance improvement, job security, and leadership.